Endocytosis and trafficking of BMP receptors: Regulatory mechanisms for fine-tuning the signaling response in different cellular contexts - Ehrlich, Marcelo (Cytokine & growth factor reviews, 2016)
[Display omitted] •TGF-β and BMP receptors localize to different membrane microdomains.•TGF-β and BMP receptors internalize mainly through clathrin mediated endocytosis.•Following endocytosis BMP receptors are sorted to one of three destinies with differing functional significance: endosomal trafficking, lysosomal degradation, or recycling to plasma membrane. Signaling by bone morphogenetic protein (BMP) receptors is regulated at multiple levels in order to ensure proper interpretation of BMP stimuli in different cellular settings. As with other signaling receptors, regulation of the amount of exposed and signaling-competent BMP receptors at the plasma-membrane is predicted to be a key mechanism in governing their signaling output. Currently, the endocytosis of BMP receptors is thought to resemble that of the structurally related transforming growth factor-β (TGF-β) receptors, as BMP receptors are constitutively internalized (independently of ligand binding), with moderate kinetics, and mostly via clathrin-mediated endocytosis. Also similar to TGF-β receptors, BMP receptors are able to signal from the plasma membrane, while internalization to endosomes may have a signal modulating effect. When at the plasma membrane, BMP receptors localize to different membrane domains including cholesterol rich domains and caveolae, suggesting a complex interplay between membrane distribution and internalization. An additional layer of complexity stems from the putative regulatory influence on the signaling and trafficking of BMP receptors exerted by ligand traps and/or co-receptors. Furthermore, the trafficking and signaling of BMP receptors are subject to alterations in cellular context. For example, genetic diseases involving changes in the expression of auxiliary factors of endocytic pathways hamper retrograde BMP signals in neurons, and perturb the regulation of synapse formation. This review summarizes current understanding of the trafficking of BMP receptors and discusses the role of trafficking in regulation of BMP signals.